Molecular Therapies - Schneider, Holm; Schneider, Pascal (Springer Nature, 2025)
This chapter describes the development of molecular therapies for X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common ectodermal dysplasia syndrome, and for the cutaneous and ocular manifestations of p63-associated syndromes. Large parts of the text are based on the following previously published journal article by Holm Schneider: “Ectodermal dysplasias: New perspectives on the treatment of so far immedicable genetic disorders”, Front Genet. 13:1000744, doi: 10.3389/fgene.2022.1000744; available under the terms of the Creative Commons Attribution License (CC BY).
CRIS-Team Scopus Importer:2025-05-02
Keywords: Ectodysplasin A; Molecular therapy; Neonatal Fc receptor; P63 PRIMA-1MET